Does Corruption Affect Income Inequality and Poverty? - Gupta, Sanjeev (Washington, D.C. : International Monetary Fund, 1998)
This paper demonstrates that high and rising corruption increases income inequality and poverty by reducing economic growth, the progressivity of the tax system, the level and effectiveness of social spending, and the formation of human capital, and by perpetuating an unequal distribution of asset ownership and unequal access to education. These findings hold for countries with different growth experiences, at different stages of development, and using various indices of corruption. An important implication of these results is that policies that reduce corruption will also lower income inequality and poverty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet